iNFLUENCE OF REGULAR HAND FIGHTING ON THE FUNCTIONAL CAPABILITIES OF THE CARDIOVASCULAR SYSTEM - Dorontsev A.V. ,; Zavalishina S.Yu. ,; Boldov A.S. ,; Vorobieva N.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to find out the consequences of vestibular irritation on the cardiovascular system of experienced hand-to-hand fighters. Methods and structure of the study. 46 young hand-to-hand fighters (19.2 ± 0.9 years) were observed, who systematically went in for sports 2-3 times a week during: 1 year - 15 persons, 2 years - 14 persons, 3 years - 17 persons. The control group consisted of 16 clinically healthy adolescents (20.0±0.5 years) who were not previously involved in sports. The physiological characteristics of the system of the heart and blood vessels were monitored under conditions of vestibular stimulation during a rotational test. Student's t-test was applied. Results and conclusions. The performance of sports movements, especially in hand-to-hand combat, makes it necessary for the athlete to develop the vestibular apparatus, which helps to maintain the optimum position of the body in space. An increase in the experience of hand-to-hand training is accompanied by an optimization of the parameters of the cardiovascular system and an increase in the functional characteristics of the vestibular apparatus. The maximum stability of the pulse value was observed in hand-to-hand fighters who had three years of experience in performing specific movements at different angles. We can assume that hand-to-hand combat trains the system of the heart and blood vessels and helps to increase its level of adaptation to vestibular irritation.